THE GLOBAL MARITIME PORTS IN LOGISTICS CHAINS AND SUPPLY NETWORKS - Henryk SALMONOWICZ (Scientific Journal of Silesian University of Technology. Series Transport, 2014)
This article applies to the new role of seaports in the global economy and logistics. The paper presents trends in the development of the world economy and the dynamics of global trade. Attention was drawn to the role of different modes of transport to use global trade, especially on transcontinental nature of sea and air transport. The influence of the processes taking place in the global economy on a new role of seaports in the mass movement of cargo between points of origin and reception.